Programa de preparação para aposentadoria da Universidade Federal do Espírito Santo entre 2017 e 2021: uma análise da percepção dos servidores participantes - Pimentel, Luiza Camporez (2023)
The process of breaking the bond with work and the transition to retirement can be one of the biggest changes in a person's life. At the same time that the individual who is facing that process creates expectations about the future free time he will enjoy, the post-career period can cause negative consequences, such as isolation, the feeling of uselessness and the loss of social relationships. Retirement preparation programs (RPP) were implemented as a way to alleviate this distressing process. In this context, the Federal University of Espírito Santo has a RPP, currently called Life and Retirement Planning, whose responsible team has been working since 2014, always seeking to improve it. One of the ways pointed out in the literature to contribute to the improvement of a PPA is to carry out evaluations with the participants throughout and at the end of the program and to carry out a follow-up for up to 5 years after retirement. In this way, the research problem is represented by the following question: to what extent does the Retirement Preparation Program had contributed or contribute to the planning and retirement process of Ufes’s public servants, retired or who are yet to retire, and how can the program become more effective? The main objective is to understand the impact of Ufes's Institutional Retirement Preparation Program on its participants, from the perspective of the servants who participated in it. In theoretical terms, the research is supported on the retirement process, the positive and negative aspects and its relationship with work, the legal aspects of retirement in the public sector in Brazil and the general panorama of retirement preparation programs, including the its characteristics, programmatic contents and structures. As for the methods and procedures, the research is classified as descriptive-explanatory type, with a qualitative approach. The nature of the collected data is primary, the sources are people and public documents. The instruments of the data collection were performed semi-structured interviews (people) and bibliographical survey (documents). As for data analysis, the content were categorized by themes. The results obtained attest to the quality and importance of the institutional retirement preparation program at Ufes, since most participants stated that the course was relevant and contributed to their planning and/or their retirement process. In addition, the participants pointed out suggestions in order to contribute to the improvement of the program. Based on the results, as a technical product, a Conclusive Technical Report was prepared in the form of a management tool, containing suggestions for improving the program.